Noncommunicable Diseases (Hypertension or Diabetes Mellitus) Among Private University Lecturers and Related Factors - Kalsum, Ummi; Andini, Melati Puti; Sitanggang, Hendra Dhermawan; Nasution, Helmi Suryani (Kesmas, 2025)
Excessive workload, lack of rest, poor diet, stress, and insufficient physical activity are some contributing factors to a high risk of noncommunicable diseases (NCDs) for lecturers. This study aimed to develop a predictive model for the risk of NCDs among lecturers at a private university in Jambi City, Indonesia. A cross-sectional design was used, and the sample included 93 lecturers who met the inclusion criteria. The independent variables were workload, rest pattern, diet, physical activity, stress, smoking, and family history. The dependent variable was NCDs (hypertension or diabetes mellitus), measured through interviews based on a doctor's diagnosis. Data analysis was performed using Cox multivariate regression analysis. The proportion of NCDs among the lecturers was 25.8%. The factors associated with NCDs include workload, rest patterns, and family history. Lecturers are advised to adopt preventive behaviors, and universities must implement early detection of NCD programs to foster health-promoting environments.